2010
DOI: 10.1111/j.1558-5646.2010.01078.x
|View full text |Cite
|
Sign up to set email alerts
|

Predator-Driven Trait Diversification in a Dragonfly Genus: Covariation in Behavioral and Morphological Antipredator Defense

Abstract: Proof for predation as an agent shaping evolutionary trait diversification is accumulating, however, our understanding how multiple antipredator traits covary due to phenotypic differentiation is still scarce. Species of the dragonfly genus Leucorrhinia

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
68
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(74 citation statements)
references
References 52 publications
3
68
3
Order By: Relevance
“…Even though we worked with field‐collected data, we did not expect selective mortality by predation or phenotypic plasticity mediating our interspecific findings, because Mikolajewski et al . () and Petrin et al . () showed that neither selective mortality nor phenotypic plasticity mediated differences in morphological, physiology and behavioural traits across Leucorrhinia species.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Even though we worked with field‐collected data, we did not expect selective mortality by predation or phenotypic plasticity mediating our interspecific findings, because Mikolajewski et al . () and Petrin et al . () showed that neither selective mortality nor phenotypic plasticity mediated differences in morphological, physiology and behavioural traits across Leucorrhinia species.…”
Section: Discussionmentioning
confidence: 97%
“…However, direction of trait change and selective strength turned out to be trait‐specific. Whereas burst swimming speed to evade predators and its associated morphological as well as physiological machinery are reduced in dragonfly lake Leucorrhinia species as a response to reduced capture efficiency of invertebrate predators (Mikolajewski et al ., ; Mikolajewski et al ., ; Mikolajewski et al ., ), larval foraging and activity are increased in dragonfly lake Leucorrhinia species (this study, Fig. ).…”
Section: Discussionmentioning
confidence: 99%
“…To control for relatedness among Leucorrhinia species, we applied phylogenetic generalized linear models (Garland et al ., ) with incorporated branch length based on the known Leucorrhinia phylogeny (Fig. ; Mikolajewski et al ., ). For each species, we only used data from individuals sampled in the species' most common habitat (e.g.…”
Section: Methodsmentioning
confidence: 97%
“…; Mikolajewski et al. ). The proximal hormonal and molecular mechanisms leading to this phenotypic integration between morphology and behaviour are still to be uncovered (Box ).…”
Section: An Organismal Evolutionary Biologist' S Journey Into the Reamentioning
confidence: 99%